Cancer immunotherapy‐targeted glypican‐3 or neoantigens - Shimizu, Yasuhiro (Cancer Sci, 2018)
Immune checkpoint inhibitors have ushered in a new era in cancer therapy, although other therapies or combinations thereof are still needed for many patients for whom these drugs are ineffective. In this light, we have identified glypican‐3 an HLA‐24, HLA‐A2 restriction peptide with extreme cancer specificity. In this paper, we summarize results from a number of related clinical trials showing that glypican‐3 peptide vaccines induce specific CTLs in most patients (UMIN Clinical Trials Registry: UMIN000001395, UMIN000005093, UMIN000002614, UMN000003696, and UMIN000006357). We also describe the current state of personalized cancer immunotherapy based on neoantigens, and assess, based on our own research and experience, the potential of such therapy to elicit cancer regression. Finally, we discuss the future direction of cancer immunotherapy.